Comparative assessment of the efficacy of gross total versus subtotal total resection in patients with glioma: A meta-analysis. (March 2019) - Tang, Shuang; Liao, Jin; Long, Yong
Abstract: Background: It is controversial whether to plan for a subtotal or gross total resection (GTR) of lesions in patients with gliomas. Several studies have demonstrated that GTR may be superior to subtotal resection (STR) with regard to improving the survival rates of patients with glioma. Thus, the present meta-analysis was designed to compare and evaluate the efficacy of GTR for improving clinical outcomes of patients with glioma. Methods: We searched the Cochrane Library, PubMed, Embase, and Web of Science for the interval between March 1972 to November 2018 to identify relevant original studies that compared the efficacy of GTR and STR in patients with gliomas. Mean differences (MDs) with 95% confidence intervals (CIs) were estimated to compare the outcomes of the GTR and STR groups. We also performed subgroup and sensitivity analyses to further explore the effects of the extent of surgical resection (EOR) and assess the stability of the combined results. Two external (blinded) reviewers assessed the quality of the trials and the extracted data independently. All statistical analyses were performed using standard statistical procedures provided in Review Manager 5.2. Results: We included 42 studies (N = 5920 participants) in this meta-analysis. Significantly superior efficacy was detected for GTR to improve overall survival compared to STR (MD 4.01, 95% CI 2.52–5.51; P  < 0.00001), 5-year survival rate (OR 4.08, 95% CI 3.02–5.52; P  < 0.00001), progression-free survival (MD 2.08, 95% CI 0.26–3.89; P =  0.02), seizure control (OR 4.25, 95% CI 2.99–6.05; P  < 0.00001), and reducing the incidence of malignant transformation (OR 0.28; 95% CI 0.13–0.60; P  = 0.001) in patients with glioma. Conclusions: Our meta-analysis supports the superior efficacy of GTR on survival, functional outcome, tumor progression, seizure control, malignant transformation, morbidity, and mortality in patients with glioma. Highlights: At present, there exists a controversy whether to plan for STR or GTR of the lesion for patients with gliomas. The analysis was designed to compare and evaluate the efficacy of GTR for improving clinical outcomes in patients with glioma. Compared with STR, significantly superior efficacy of GTR was found in improving the survival. GTR also benefited glioma in improving seizure control as well as in reducing the incidence of malignant transformation.